VD_FINDINFO HC / 2020 / 771 vom 26. Februar 2021 - VD Tribunal cantonal (2021)
ÉGALITÉ ENTRE HOMME ET FEMME, ÉGALITÉ DE RÉMUNÉRATION, LIBERTÉ CONTRACTUELLE, PREUVE FACILITÉE | 322 CO, 328 al. 1 CO, 8 Cst., 3 LEg, 6 LEg